The Effect of the Regional Security Events on Commercial Banks Financial Performance in KRG: Effect of the Regional Security Events on Commercial Banks (Academic Journal of International University of Erbil, 2018)
This study attempts principally to measure the financial performance of Kurdistan International Bank which is one of the largest and prominent private commercial banks in Kurdistan and to find if any difference exists between two periods of operation, these periods are (2010-2012 & 2013-2015). The researchers used financial ratio analysis method which help to make an overview about financial performance of the Kurdistan International Bank in terms of profitability, liquidity and credit performance.To test the hypothesis the researchers have used SPSS to compare between the performance of the bank during these two phases (2010-2012 & 2013-2015); where the study could not include the 2016 because the financial results for 2016 has not been published yet. These analyses help to see the current performance condition of this bank compared with past performance because at the present time banking sector of Kurdistan is suffering the existence of default culture which is the result of bad performance of most banks especially in the time of bad security situation. The performance of commercial banks is dependent more on the management's skill in framing strategic plans and the effective implementation of its strategies. The study findings can be helpful for management of Kurdistan International Bank to improve their financial performance and putting policies that will improve their performance. The study also identifies specific areas for banks to develop which can ensure viable growth for these banks.